2019
DOI: 10.20473/j.djmkg.v52.i3.p147-153
|View full text |Cite
|
Sign up to set email alerts
|

Closed reduction in the treatment of neglected mandibular fractures at the Department of Oral and Maxillofacial Surgery, Universitas Airlangga

Abstract: Background: The mandible is one of the bones most affected by facial fractures commonly resulting from trauma to the face. The ultimate goal of treatment is to re-establish the pre-injury dental occlusion (bite), mandibular anatomy and jaw function of the patient. Treatment approaches range from conservative non-invasive management by ’closed’ reduction and immobilization using intermaxillary fixation (IMF) to the more invasive surgery-based ’open’ reduction incorporating an internal fixation approach. Purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Twenty-six studies revealed the potential effect of GSE on the alveolar bone, including maxilla, 15 interpremaxillary, 34 alveolar bone in a molar area, 35 36 37 and incisive area 38 39 the mandibular jaw bone 40 41 and condyle 31 42 skeletal bone including the femur, 28 43 calvaria, 28 and tibia. 28 44 45 46 47 In the disease model, femur, 48 49 50 51 52 tibia, 53 54 and knee were used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-six studies revealed the potential effect of GSE on the alveolar bone, including maxilla, 15 interpremaxillary, 34 alveolar bone in a molar area, 35 36 37 and incisive area 38 39 the mandibular jaw bone 40 41 and condyle 31 42 skeletal bone including the femur, 28 43 calvaria, 28 and tibia. 28 44 45 46 47 In the disease model, femur, 48 49 50 51 52 tibia, 53 54 and knee were used.…”
Section: Resultsmentioning
confidence: 99%
“…The study of supplementations of GSE was mostly performed in Wistar rats, 15 31 35 36 37 38 40 41 42 43 44 45 46 47 49 50 54 55 Sprague-Dawley rat, 34 rabbits, 39 51 52 and mice. 28 48 56…”
Section: Resultsmentioning
confidence: 99%
“…This result is in accordance with the statement of Sultana et al, who stated that the prominent position of the mandible in the facial region is prone to trauma, especially in the parasymphysis region. 12 Various pieces of literature also state that the anatomical location of mandibular fractures is influenced by several other factors, such as the mechanism of injury, the direction of trauma, the magnitude of the trauma, and the characteristics of each person's mandible. 6,9,11 The data of this study stated that the most mandibular fracture treatment at RSUP Dr. Hasan Sadikin Hospital during the study period was the open reduction, as many as 197 patients (82.03%).…”
Section: Discussionmentioning
confidence: 99%
“…11 Ultimate goal of treatment is to re-establish the preinjury dental occlusion (bite), mandibular anatomy and jaw function of the patient. 12 Reduction techniques in mandibular fracture treatment may be classified as open or closed depending on the presence or absence of direct visual access to the fracture site. 13 RSUP Dr. Hasan Sadikin General Hospital, the highest and biggest referral hospital in west java, receives many mandibular fracture cases.…”
Section: Introductionmentioning
confidence: 99%
“…The primary objective of the treatment is to reconstruct the pre-injury dental occlusion, as well as the mandibular anatomy and jaw function. The therapeutic management consists of soft diet, closed reduction with intermaxillary fixation (bonded orthodontic brackets, arch bars, direct wires, eyelet wires), and open reduction with internal fixation (wires, plates, hard wares placed directly across the fractured site) [19,22,23].…”
Section: Mandibular Fractures-general Conceptsmentioning
confidence: 99%